Kemampuan Berpikir Kreatif Matematika Siswa melalui Pendekatan Pembelajaran Open-Ended - Apriliani Defri, Dinny; Fitri, Haida; Zakir, Supratman; Isnaniah, Isnaniah (Lembaga Yasin AlSys, 2025)
This study is motivated by the low creative mathematical thinking ability of eighth-grade students at SMP IT Al-Khansa Rengat. The students seem unable to come up with many different solutions or approaches, so an instructional approach is needed to address this issue. The approach that is believed to overcome this problem is the open-ended approach. The research question of this study is: “Is the creative mathematical thinking ability of students who follow the open-ended learning approach better than those who follow conventional learning in the eighth grade at SMP IT Al-Khansa Rengat?” The objective is to determine whether the creative mathematical thinking ability of students who follow the open-ended approach is better than those who follow conventional learning in the eighth grade at SMP IT Al-Khansa Rengat. The hypothesis of this study is that the creative mathematical thinking ability of students who follow the open-ended approach is better than those who follow conventional learning at SMP IT Al-Khansa Rengat. The data analysis technique used is the t test and Minitab software. The results of the analysis obtained tcount=3.114 and ttable=2.120. Because 3.114>2.120, the conclusion is that H0 is rejected and H is accepted. It can be concluded the creative thinking abilities in mathematics of students who take part in learning using an open ended approach are better than students who take part in conventional learning in class VIII SMP IT Al-Khansa Rengat.